PENGARUH INFORMASI PRODUK, KESAN DAN ATURAN SOSIAL SERTA KESENANGAN TERHADAP OPTIMASI STRATEGI PERIKLANAN MELALUI APRESIASI IKLAN PADA PRODUK SABUN MANDI LUX DAN LIFEBUOY (STUDI PADA IBU RUMAH TANGGA DI KOTA SEMARANG) - Utaminingsih, Adiyati; Rahardjo, Daryono; Sulistyorini, Utami Tri (JURNAL BISNIS STRATEGI, 2002)
Advertising is an important social phenomenon. It stimulates consump tion, economic activity, models life styles, and a certain value orientation. Consumers are confronted with subtantial daily doses of advertising in multiple media. Everyone seems to  hold an opinion about various aspects of advertising ranging from amusement and admiration to cynicism and condemnation.Most advertisers agree that optimal advertising strategy should consider qualitative factors, such as  audience involvement.  This paper examines the research on qualitiative factors and how to incorporate them into the optimization process. It is believed that such research is impor tant because better knowledge about qualitative viewing factors will improve the planning and optimization process.